Temperature and salinity fluctuations in the Norwegian Sea in relation to wind - Mork, Kjell Arne; Asplin, Lars (ICES, 1999)
Hydrographic observations in the Svinøy section and results from the Princeton Ocean Modei are used to investigate the role the wind forcing has on temperature and salinity fluctuations in the Nonvegian Sea. In order to investigate the role the wind forcing has on observed fluctuations in the Norwegian Sea the model is driven for two different air pressure regimes. A period from the 1960s with a relatively low NAO index is used for one regime while a period from the 1990s with a relatively high NAO index is used for the other regime. Wind data used in the model are from the Hindcast data base archive from the Norwegian Meteorological Institute. The period with high NAO index caused a freshening and cooling of the upper layers in the central Norwegian Sea relative to the period wiih low NAO index. Thls was caused by a reduced transport of Atlantic water over the Iceland-Faeroe Ridge and at the same time the transport through the Faeroe-Shetland increased. In the period with low NAO index the opposite case occured.